Measurement of Digital Service Quality and Success of District Library Information System (SIPERKA) Implementation: Integration of HOT-Fit Model and Service Quality Dimensions - Rian Piarna; Masesa Angga Wijaya; Agin Sugiwa; Liandy L Tobing; Wulan Siti Nurul Masriah; Muthiah Wahyuliana (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
This study evaluates the success of District Library Information System (SIPERKA) implementation in Subang Regency using the integration of HOT-Fit (Human, Organization, Technology-Fit) model and service quality dimensions. Employing SEM-PLS methodology with 115 village librarians and library operators, the research examines how Technology components (system quality, information quality, service quality), Human factors (user satisfaction, user competency, system use), and Organizational aspects (organizational structure, leadership support, environment) collectively influence net benefits. Results demonstrate that service quality exerts the strongest influence (β=0.312) on user satisfaction among technological dimensions, while system use (β=0.468) emerges as the primary determinant of net benefits. The integrated model explains 71.5%-76.8% variance in endogenous variables with Goodness of Fit (GoF) of 0.719, indicating excellent model performance. All ten hypotheses received empirical support (p<0.05). This research contributes theoretically by demonstrating the critical importance of service marketing perspective in public sector information systems evaluation, revealing that service quality supersedes technical quality in determining user satisfaction. Practically, it provides evidence-based recommendations for improving digital service quality in village libraries, with documented Return on Investment (ROI) of 630.8% demonstrating SIPERKA's success in elevating village library data achievement from below 40% to 87%.